Non-ionizing radiation (NIR) exposure map development using GIS for Gong Badak, Terengganu, Malaysia - Hazmin, S.N; Dianah, A.R.S.N.; Kamarudin, M. K. A.; Umar, R.; Syafiqah, H.N. (2018)
Public Non-Ionizing Radiation (NIR) exposure should be monitored by the government since it has proven harmful for human. Even though some studies reported that low frequency spectrum is safe, the other says that long and repetitive exposure may aﬀect health. Thus, this study is conducted to measure the ambient NIR exposure value in the selected Terengganu area, Malaysia. The values were then used to develop a spatial model of exposure to see the radiation exposure pattern. From the ﬁndings, we found that the value was higher nearby base stations which are normally erected around residential area where the telecommunication network user is high. Thus, this study is crucial to determine the level of exposure for future plan. This ﬁndings can be used by the government to control the radiofrequency transmission and active spectrum service provider in order to limit the radiation exposure for public health concern.